NEXUS BETWEEN ASYMMETRIC INFORMATION AND STOCK MARKET VOLATILITY: EVIDENCE FROM SRI LANKA - Hewamana, H. M. R. R.; Siriwardhane, D. R. J.; Rathnayake, R. M. A. K. (My University, 2021)
Stock price volatility is an essential phenomenon in equity valuation, derivatives markets, risk management, and portfolio investment decisions. The right measurement of stock volatility is a demanded task among the equity investment community. Volatility clustering and volatility persistence are successful assumptions on stock volatility modeling and forecasting. These two volatility assumptions are mainly driven by the impact of market news on fundamental factors of equity securities. However, there may have differences in distribution of information between market participants. As a result of that stock price volatilities may exhibit irrational behaviors which cannot be explained with fundamental market news

Therefore, fundamental volatility determinants deliver inconsistence empirical research findings irrespective of the market and its size. This study has examined the impact of asymmetric information in modeling the stock price volatility with relating to the Colombo Stock Exchange (CSE) market. In addition to that the role of macroeconomic variability has been examined for determining the CSE price volatilities. The EGARCH statistical method was undertaken to identify the impact of asymmetric information behavior in modeling the stock price volatility whereasthe Gross Domestic Production (GDP), inflation, interest rate, and money supply have been modeled as explanatory control variables with different Auto Regressive (AR) lags

The study has identified that the CSE market shows significant asymmetric information distribution behavior with negative volatility leverage. The inflation and money supply have significant influence on CSE volatility, however, GDP has little explanatory power. Furthermore, it was found that CSE price volatility has taken few weeks for responding to the macroeconomic variability based on lag interval results.
Keywords: Stock Volatility, Asymmetric Information, Macroeconomics, EGARCH